2017
DOI: 10.15578/squalen.v11i2.250
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Lyase from Indonesian Bacillus megaterium S245 Shows Activities Toward Polymannuronate and Polyguluronate

Abstract: Screening of alginate lyase producing bacteria associated with seaweed Sargassum crassifolium was carried out, and isolate S245, identified as Bacillus megaterium S245 was found to produce high alginate lyase activity. This research was conducted to evaluate activity of the alginate lyase enzyme at various pHs, temperatures and substrates. Polymannuronate and polyguluronate were used to evaluate substrate specificities. Alginate lyase activity was assayed by analysis of reducing sugar released using the 3,5 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Pada penelitian sebelumnya, telah diperoleh isolat bakteri Bacillus megaterium strain baru yaitu Bacillus megaterium SS4b yang memiliki kemampuan menghasilkan alginat lyase dan dapat digunakan dalam produksi oligosakarida alginat (Subaryono et al, 2015;Subaryono et al, 2016). Bakteri B. megaterium SS4b tersebut juga dilaporkan mampu menyekresikan enzim-enzim ekstraseluler seperti amilase, protease maupun selulase (Mulyasari et al, 2015).…”
Section: Pendahuluanunclassified
“…Pada penelitian sebelumnya, telah diperoleh isolat bakteri Bacillus megaterium strain baru yaitu Bacillus megaterium SS4b yang memiliki kemampuan menghasilkan alginat lyase dan dapat digunakan dalam produksi oligosakarida alginat (Subaryono et al, 2015;Subaryono et al, 2016). Bakteri B. megaterium SS4b tersebut juga dilaporkan mampu menyekresikan enzim-enzim ekstraseluler seperti amilase, protease maupun selulase (Mulyasari et al, 2015).…”
Section: Pendahuluanunclassified
“…Heryandi et al (2018) reported fermented of pineapple peel waste could be used in broiler diet up to 12% without negative effects on organ development and carcass performance. Subaryono et al (2016) reported, bacterium Bacillus megaterium S245 produce alginate lyase This bacterium includes of negative gram bacterium which was isolated from Sargassum crassifolium brown seaweed. Furthermore, it is explained this enzyme can depolymerize polymanuronate or polyguluronate from alginate structure, this bacterium also was used to produce oligosaccharides alginate from alginate (Subaryono et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subaryono et al (2016) reported, bacterium Bacillus megaterium S245 produce alginate lyase This bacterium includes of negative gram bacterium which was isolated from Sargassum crassifolium brown seaweed. Furthermore, it is explained this enzyme can depolymerize polymanuronate or polyguluronate from alginate structure, this bacterium also was used to produce oligosaccharides alginate from alginate (Subaryono et al, 2016). So far, there is no report regarding the utilization of Bacillus megaterium S245 as inoculum to ferment Sargassum binderi brown seaweed for lowering its alginate content thought fermentation method, in feed of laying hens.…”
Section: Introductionmentioning
confidence: 99%